Image Enhancement Technique based on Interpolation of Noise Image for Closed Circuit Television - Kingboo, Athaporn; Sodanil, Maleerat (Journal of Advanced Development in Engineering and Science, 2023)
The Closed Circuit Television (CCTV) was a great device for recording a wholesome image and moving well, it can be used to recorded events that occur at any time. However, there has been a problem with resolution and sharpness form the CCTV. This is caused by the features of the CCTV system and various recording environments, affecting the image from the recording to be noise or blur. This research proposed an image enhancement technique for low-quality CCTV caused by noise in terms of resolution and sharpness, using the Interpolation-Based Technique (IB-T). The experiments are conducted using by a set of enlarged image. PSNR and SSIM are used to measure the performances of proposed technique, and also compared other techniques. The results show that this technique can be used for image enhancement.